Repression of apical homeobox genes is required for embryonic root development in Arabidopsis. - Grigg, S; Galinha, C; Kornet, N; Canales, C; Scheres, B; Tsiantis, M (2009)
Development of seed plant embryos is polarized along the apical-basal axis. This polarization occurs in the absence of cell migration and culminates in the establishment of two distinct pluripotent cell populations: the shoot apical meristem (SAM) and root meristem (RM), which postembryonically give rise to the entire shoot and root systems of the plant. The acquisition of genetic pathways that delimit root from shoot during embryogenesis must have played a pivotal role during land plant evolution because roots evolved after shoots in ancestral vascular plants and may be shoot-derived organs. However, such pathways are very poorly understood. Here we show that RM establishment in the model plant Arabidopsis thaliana requires apical confinement of the Class III HOMEODOMAIN-LEUCINE ZIPPER (HD-ZIP III) proteins PHABULOSA (PHB) and PHAVOLUTA (PHV), which direct both SAM development and shoot lateral organ polarity. Failure to restrict PHB and PHV expression apically via a microRNA-dependent pathway prevents correct elaboration of the embryonic root development program and results in embryo lethality. As such, repression of a fundamental shoot development pathway is essential for correct root development. Additionally, our data suggest that a single patterning process, based on HD-ZIP III repression, mediates both apical-basal and radial polarity in the embryo and lateral organ polarity in the shoot.